2021
DOI: 10.1093/heapro/daab047
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review: global health literacy interventions for pregnant women and mothers with young children

Abstract: Summary The World Health Organization is focused on enhancing health literacy (HL) throughout the life-course to address the growing burden of non-communicable diseases (NCDs) globally. Pregnancy and early motherhood offer a window of opportunity to address NCDs risk earlier in the life-course. Empowering women through HL may help to reduce the intergenerational impact of NCDs. A scoping review of the international literature was conducted to identify HL interventions that focused on improving N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
0
9
0
Order By: Relevance
“…This has implications for policymakers and health systems to ensure that the health needs of women are addressed, and support services are sustained beyond the pregnancy, so women receive extended support to engage in healthy lifestyle practices during pregnancy and beyond. 19 Participants without chronic health conditions demonstrated higher health literacy levels than those with chronic health conditions, with small to medium ES noted. This finding is supported by other research which has shown that people with chronic health conditions are more likely to have more health literacy challenges.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This has implications for policymakers and health systems to ensure that the health needs of women are addressed, and support services are sustained beyond the pregnancy, so women receive extended support to engage in healthy lifestyle practices during pregnancy and beyond. 19 Participants without chronic health conditions demonstrated higher health literacy levels than those with chronic health conditions, with small to medium ES noted. This finding is supported by other research which has shown that people with chronic health conditions are more likely to have more health literacy challenges.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, women may require extended support from health and social services to maintain their health and optimally care for their children. This has implications for policymakers and health systems to ensure that the health needs of women are addressed, and support services are sustained beyond the pregnancy, so women receive extended support to engage in healthy lifestyle practices during pregnancy and beyond 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although little is known about how to strengthen HL in the group of pregnant women or new parents, ( Melwani et al, 2022 ; Nawabi et al, 2021 ) previous research indicates how HL can be increased in the general adult population. Systematic reviews of interventions to strengthen HL skills showed an overall benefit of clear health communication strategies, self-management support, empowerment, and supportive and caring environments ( Hersh et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…In regions where formula feeding is predominant, health care providers may assist in initiating the conversation about infant feeding choice early in pregnancy in a non-threatening, non-judgmental manner (Lyons et al, 2021). Prenatal visits provide opportunities to share information to facilitate an informed decision, explore the mother's concerns and beliefs and to link with community-based support programs (Melwani et al, 2021). The convenience associated with formula feeding is a belief that was held by the women in the Canadian qualitative study by Pemo et al (2020).…”
Section: Attitude Towards Exclusive Breastfeedingmentioning
confidence: 99%